INTEGRASI NILAI SYARIAH DALAM PRAKTIK KEWIRAUSAHAAN ISLAMI: TINJAUAN HABLUMMINALLAH DAN HABLUMMINANNAS - Nurlaela; Alisya Hanifah Bilqis; Neysa Afmadesikha (CV. Denasya Smart Publisher, 2025)
Islamic entrepreneurship emerges as an ethical alternative to conventional business practices that often ignore spiritual and social values. In this context, sharia values play an important role in shaping the mindset and behavior of Muslim business actors through the integration of relationships with God (hablumminallah) and fellow humans (hablumminannas). This research aims to theoretically examine the integration of sharia values in Islamic entrepreneurship, with a focus on motivation, ethics, social responsibility, and the efforts of business actors in maintaining a balance between spirituality and professionalism. The method used is a literature study that examines theories and previous findings related to Islamic business ethics and the concept of maqasid al-syariah. The results show that Islamic entrepreneurship does not only encourage the achievement of material benefits, but also emphasizes social benefits and business blessings. The implication is that Muslim business actors need to build business practices that are not only professionally competitive, but also reflect the values of justice, honesty and spiritual responsibility in every business decision